2001
DOI: 10.1002/ana.1007
|View full text |Cite
|
Sign up to set email alerts
|

Diminished adenosine A1 receptor expression on macrophages in brain and blood of patients with multiple sclerosis

Abstract: The nucleoside adenosine has been shown to control the production of proinflammatory molecules through its actions on cell surface purine receptors. Previously, we have reported that the adenosine A1 receptor (A1AR) regulates tumor necrosis factor-alpha (TNF-alpha) and interleukin-6 (IL-6) expression and exhibits diminished function in patients with multiple sclerosis (MS; Mayne et al., Ann Neurol 1999;45:633-639). In the present study, A1AR expression in both brain and peripheral blood mononuclear cells (PBMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 47 publications
2
51
0
1
Order By: Relevance
“…Reports of αCD45 labeling of microglia vary (1, 7, 13, 24, 33, 46, 56). We tested immunohistochemical techniques with differing sensitivity to determine whether microglial CD45 immunoreactivity varies depending on the technique and cell type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of αCD45 labeling of microglia vary (1, 7, 13, 24, 33, 46, 56). We tested immunohistochemical techniques with differing sensitivity to determine whether microglial CD45 immunoreactivity varies depending on the technique and cell type.…”
Section: Resultsmentioning
confidence: 99%
“…In AIDS dementia and HIV encephalitis (HIVE), microglia and macrophages are productively infected by HIV-1 and show diffuse inflammatory activation, which ultimately leads to neuronal damage and CNS dysfunction (7, 11, 14, 43). Microglia in normal human brain express CD45 and increases in microglial CD45 expression have been detected in Alzheimer’s disease, graft-versus-host disease, multiple sclerosis, and in HIVE (1, 7, 24, 30, 33, 46). Furthermore, studies in rodent and human cells suggest that CD45 can downregulate microglial activation.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the other adenosine receptor-A1R, several lines of evidence have showed that A1R may have the protective function in EAE. Firstly, the expression of A1R is reduced in MS patients [40]. Secondly, A1R-deficient mice show more severe forms of progressive and relapsing EAE compared to WT mice [41].…”
Section: Adenosine Pathway Changes In Human Autoimmune Diseasesmentioning
confidence: 99%
“…Secondly, A1R-deficient mice show more severe forms of progressive and relapsing EAE compared to WT mice [41]. Thirdly, activation of A1R reduces inflammatory response in the CNS [40]. These results demonstrate the different role of adenosinergic pathway-related molecules in MS development.…”
Section: Adenosine Pathway Changes In Human Autoimmune Diseasesmentioning
confidence: 99%
“…However, obtaining CNS mRNAs presents insurmountable ethical issues. It is possible to avoid these limitations by detecting and/or measuring central mRNAs in peripheral tissues; one such source is the peripheral blood, which is easy to obtain and known to interact with the CNS (Ledoux et al, 1995;Chuang et al, 1995;Johnston et al, 2001;Blanco-Jerez et al, 2002;Gielen et al, 2003). In particular, the best source of mRNA is represented by isolated peripheral blood mononuclear cells (PBMC), since hemoglobin (Hb) from erythrocytes can inhibit PCR amplification (Furuya et al, 1999).…”
Section: Introductionmentioning
confidence: 99%